Use of Google Classroom Media in the Effectiveness of Class X Science Learning for Odd Semester 2021-2022 Academic Year During the Pandemic Period in Class IX of SMP Negeri 1 Kuaro - Setiaji, Slamet (PT Literasi Nusantara Publisher, 2022)
This paper aims to 1) describe the implementation of science learning through Google Classroom media, 2) describe the supporting and inhibiting factors of Google Classroom for the implementation of science learning, 3) describe the effectiveness of science learning through Google Classroom media on student learning outcomes in class IX SMP Negeri 1 Kuaro. To solve the description above, the approach used is a qualitative approach, with a descriptive research type, data collection using interviews, observation, and documentation techniques. Meanwhile, data analysis was carried out by collecting data, reducing data, submitting data, and drawing conclusions. Based on data analysis it was found that 1) Implementation of science learning through google classroom media makes it easier for a teacher to convey information in the form of material to students. The purpose of implementing video applications in education is to manipulate the abstractness of the modules and concepts contained in science lessons. 2) supporting factors in terms of infrastructure availability, one of which is easy access via computers and smartphones, besides that the Google form can be accessed anywhere and anytime. The application of google classroom media in the implementation of science learning has its own positive value for students, this is evidenced by showing videos of students easily solving concepts that are still abstract in nature. The inhibiting factors are influenced by the availability of facilities and the ability to run video media and the Google form itself. In addition, the devices owned by students are not yet supported. 3) the effectiveness of science learning through google classroom media on student learning outcomes is very effective because it can make it easier for students to do assignments and collect them, even though there is still a lack of interest and awareness of students in completing assignments